1980
DOI: 10.1111/j.1365-2265.1980.tb03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intranasal LHRH Therapy on Plasma Lh, FSH and Testosterone, and Relation to Clinical Results in Prepubertal Boys With Cryptorchidism

Abstract: Synthetic LHRH (HOE 471) administered intranasally over a period of 4 weeks for treatment of uni- or bilateral cryptorchidism in nineteen otherwise healthy prepubertal boys led to increased basal and peak LH values and to markedly decreased peak FSH values in the i.v. LHRH test. Basal testosterone remained unchanged. Sixteen cryptorchid boys treated with placebo served as a control group. The reduced FSH response to i.v. LHRH could be due to induction of a gonadal feedback mechanism rather than pituitary deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Illig et al [10,11] and Pirazzoli et al [13] confirmed this finding, correlating the results with age, the position of the testis [11,13] and with the pituitary reserve of gonadotropins before and after therapy.…”
Section: Introductionsupporting
confidence: 79%
“…Illig et al [10,11] and Pirazzoli et al [13] confirmed this finding, correlating the results with age, the position of the testis [11,13] and with the pituitary reserve of gonadotropins before and after therapy.…”
Section: Introductionsupporting
confidence: 79%
“…There is some evidence that gonadotropins may exert a direct action, FSH being of importance (Illig et al, 1980).…”
Section: Results (Fig 1)mentioning
confidence: 98%
“…LHRH test. These results are in line with those of some of the previous studies (Happ et af., 1978;Illig et al, 1980;Hagberg & Westphal, 1982;Karpe et al, 1983), but contrary to others which found no changes (Pirazzoli et al, 1978;Spona et al, 1979;Hadziselirnovic et al, 1980;De Muinck Keizer-Schrama et af., 1984). The decreased FSH response to LHRH, found in our study, confirms the findings of most previous studies.…”
Section: Discussionmentioning
confidence: 74%